MAIN DIRECTIONS FOR DEVELOPING SOCIAL ENTREPRENEURSHIP IN THE REGION - Nasretdinova Farangis Odilovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
This article examines the main directions for the development of social entrepreneurship in the region and its role in solving socio-economic problems. Social entrepreneurship is considered an important mechanism that combines business activity with social responsibility and aims to address issues such as unemployment, poverty reduction, social inclusion, and improvement of living standards. The study analyzes the institutional, financial, and organizational conditions necessary for the effective development of social entrepreneurship at the regional level. Special attention is given to the role of government support, innovative business models, and cooperation between public, private, and non-profit sectors. The article also highlights international experiences and outlines practical recommendations for strengthening the ecosystem of social entrepreneurship in the regions.